Green Sukuk Development Strategy in Indonesia: ANP-SWOT Approach - Alhaq, Khairanisa; Nursyamsiah, Tita; Muthohharoh, Marhamah (Ekonomi Syariah IAIN Kudus, 2023)
Green sukuk are State Sharia Securities (SBSN) that put forward the concept of financing programs for environmentally friendly projects. However, since the issuance of this instrument, the number of green sukuk is still small compared to other SBSNs. This study aims to identify strengths, weaknesses, opportunities, threats, and solutions and develop strategies for developing green sukuk in Indonesia. The Analytic Network Process with a SWOT (Strength-Weakness-Opportunity-Threat) network structure is used. Respondents in the study amounted to five experts, consisting of academics, regulators, and practitioners. The results show that opportunities are a top priority in supporting the development of green sukuk. The most influential variables of strengths, weaknesses, opportunities, and threats are green sukuk which impacts reducing greenhouse emissions and preserving the environment. The number and types of funded projects are limited, increasing public awareness of environmentally friendly sustainable lifestyle trends and reputational risks. The priority strategy for developing green sukuk in Indonesia is increasing awareness of the issue of climate change.